The impact of intensive multifactorial treatment on perceptions of chronic care among individuals with screen‐detected diabetes: results from the ADDITION‐Denmark trial. Issue 4 (7th November 2014) - Kuznetsov, L.; Simmons, R. K.; Sandbaek, A.; Maindal, H. T.
Summary: Objectives: To describe perceptions of chronic care among diabetes patients 6 years after diagnosis by screening and to examine the impact of intensive treatment on patients' perceptions of chronic care. Methods: The ADDITION‐Denmark (2001–2006) trial compared the effects of intensive multifactorial therapy (IT) with routine care (RC) among individuals with screen‐detected diabetes. Perceptions of chronic care were assessed using the Patient Assessment of Chronic Illness Care (PACIC) measure after 6‐year follow‐up ( n  = 937). Analysis was by intention‐to‐treat, accounting for clustering by general practice. Results: The mean (SD) summary PACIC score was 2.4 (0.79) in the RC and 2.4 (0.82) in the IT group. The highest mean (SD) PACIC subscale score was for Delivery System Design/Decision Support [RC: 3.2 (0.95), IT: 3.3 (0.91)] and the lowest was for Follow‐up/Coordination [RC: 2.1 (0.84), IT: 2.1 (0.87)]. Perceptions of chronic care did not differ between trial groups. Conclusions: Compared to RC, an intensive multifactorial intervention was not associated with differences in perceptions of chronic care among patients with screen‐detected diabetes after 6 years. Intensive treatment does not adversely affect perceptions of chronic care early in the course of the disease. However, there is potentially room for improvement in some aspects of chronic care.